2012
DOI: 10.1590/s0004-27492012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year results of phototherapeutic keratectomy on recurrent corneal erosions

Abstract: Purpose: To determine the ten-year visual results and outcomes of excimer laser pho totherapeutic keratectomy (PTK) for recurrent corneal erosions. Methods: Twenty-six eyes of 23 patients with recurrent corneal erosions were treated by PTK from 1996 to 2000 at the Goiania Eye Institute, Brazil. All eyes had failed to respond to conventional therapy. Data regarding preoperative and postopera ti ve best-spectacle-corrected visual acuity (BSCVA), spherical equivalent (SE), sympto matic relief, incidence of recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…[15] Using the PTK technique, superficial corneal opacification can be ablated, leaving the clear underlying stroma undisturbed. The PTK can be recommended in cases of corneal dystrophies, [2,6–9] band keratopathy (BK), [10] recurrent corneal erosion, [1113] and certain types of degenerative corneal diseases. [1416] PTK is thought to be a minimally invasive therapy for an anterior corneal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Using the PTK technique, superficial corneal opacification can be ablated, leaving the clear underlying stroma undisturbed. The PTK can be recommended in cases of corneal dystrophies, [2,6–9] band keratopathy (BK), [10] recurrent corneal erosion, [1113] and certain types of degenerative corneal diseases. [1416] PTK is thought to be a minimally invasive therapy for an anterior corneal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] PTK is performed with manual removal of the loosely adherent epithelium, followed by ablation of the abnormal basement membrane and superficial stroma using excimer laser (193 nm). [ 17 ] A 10-year study showed that recurrence of painful corneal erosions occurred in 6 eyes (23.07%) after PTK, which required a PTK retreatment. The mean change in spherical equivalent manifest refraction was +0.08 ± 0.30 D compared to the preoperative refraction.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent corneal erosions can be seen in association with corneal dystrophies such as EBMD and LCD or they can be nondystrophic in origin, developing after trauma, or be idiopathic in nature. 129 Clinically they present with acute episodes of pain, lacrimation, and photophobia, usually at night or upon awakening. 199 Conservative treatment options help in temporarily alleviating symptoms but do not alter the underlying disease process.…”
Section: Recurrent Corneal Erosionsmentioning
confidence: 99%
“…28 Studies of PTK performed for RCEs report high recurrence rates in the eyes with nontraumatic origin of erosions attributed to an underlying corneal dystrophy. 20,67,129 Recurrence rates range from 0 to 42%, 20,28,67,144,182 with a recurrence-free interval ranging from as early as 6 to 9 months 20,33,50,111,171 to up to 21 months 15 after treatment.…”
Section: Recurrence Of Diseasementioning
confidence: 99%